The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/jxb/erv278
|View full text |Cite
|
Sign up to set email alerts
|

The maizefused leaves1(fdl1) gene controls organ separation in the embryo and seedling shoot and promotes coleoptile opening

Abstract: HighlightThis study provides the first characterization of an R2R3 family MYB transcription factor involved in cuticle and epicuticular wax deposition, whose action is confined to maize embryogenesis and juvenile phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 53 publications
9
35
0
Order By: Relevance
“…Homozygous fdl1-Mu mutant plants showed organ fusion defects at the seedling stage (Supplemental Figure 5). Similar to ad1 mutants, a reduced amount of epicuticular wax crystals, increased loss of epidermal water and faster chlorophyll leaching were also observed in fdl1-Mu plants (Supplemental Figure 5) mirroring what was previously reported for another fdl1 allele (La Rocca et al, 2015). Using RNA in situ hybridizations, we determined that FDL1 showed strong expression in the epidermal layer of young leaves and tassels, in a pattern remarkably similar to AD1 ( Figure 5B, Supplemental Figure 5).…”
Section: The Myb Transcription Factor Fused Leaves1 Positively Regulasupporting
confidence: 82%
See 3 more Smart Citations
“…Homozygous fdl1-Mu mutant plants showed organ fusion defects at the seedling stage (Supplemental Figure 5). Similar to ad1 mutants, a reduced amount of epicuticular wax crystals, increased loss of epidermal water and faster chlorophyll leaching were also observed in fdl1-Mu plants (Supplemental Figure 5) mirroring what was previously reported for another fdl1 allele (La Rocca et al, 2015). Using RNA in situ hybridizations, we determined that FDL1 showed strong expression in the epidermal layer of young leaves and tassels, in a pattern remarkably similar to AD1 ( Figure 5B, Supplemental Figure 5).…”
Section: The Myb Transcription Factor Fused Leaves1 Positively Regulasupporting
confidence: 82%
“…wax1, wax2, lcr, hth and lacs1 lacs2) indicating that cuticle formation involves a complex array of components, each critical for plant development (Jenks et al, 1996;Wellesen et al, 2001;Chen et al, 2003;Kurdyukov et al, 2006b;Kurdyukov et al, 2006a;Bird et al, 2007;Panikashvili et al, 2007;Weng et al, 2010). While the mechanism of how wax and cutin biosynthetic pathway mutants affect cuticle structure, composition and properties is not well understood, it is clear that proper cuticle formation which starts from L1 cells during embryo development, plays an essential role in maintaining organ separation and preventing postgenital fusions (Yephremov et al, 1999;Pruitt et al, 2000;Ingram and Nawrath, 2017) Genome-wide DAP-seq analysis indicated that FDL1, a previously described MYB TF (La Rocca et al, 2015), directly binds to many genes involved in wax biosynthesis, including those encoding enzymes, transporters and upstream transcriptional regulators. A major category of targets bound by FDL1 and validated by qRT-PCR belongs to the KCS gene family, including AD1 itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In concert with stomata, the cuticle acts as an interface between plants and their surrounding environment, protecting them against a variety of biotic and abiotic stresses (Chen et al, ; Reina‐Pinto & Yephremov, ; Yeats & Rose, ). The cuticle also plays an essential role in plant development during pollen maturation (Shi, Cui, Yang, Kim, & Zhang, ; Zhang, Yang, & Shi, ) and in preventing organ fusion during seedling development (Kurdyukov et al, ; La Rocca et al, ; Luo, Xue, Hu, Wang, & Chen, ). However, the most important function of the cuticle is to protect aerial plant tissues and organs against water loss (Aharoni et al, ; Borisjuk, Hrmova, & Lopato, ; Yeats & Rose, ).…”
Section: Introductionmentioning
confidence: 99%